2004
DOI: 10.1002/jmri.20104
|View full text |Cite
|
Sign up to set email alerts
|

MRI of helium‐3 gas in healthy lungs: Posture related variations of alveolar size

Abstract: Purpose:To probe the variation of alveolar size in healthy lung tissue as a function of posture using diffusionweighted helium-3 hyperpolarized gas imaging. Materials and Methods:Measurements of the helium-3 apparent diffusion coefficient (ADC) were made on six healthy subjects. These were used to show the variation of alveolar size between the lowermost dependent regions of the lung compared to the uppermost regions of the lung in four postures: supine, prone, left-lateral decubitus, and right-lateral decubit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
72
3
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 17 publications
(28 reference statements)
11
72
3
1
Order By: Relevance
“…The heart and abdomen also contribute to the greater compression of the posterior lung regions in the supine position (23). Gravitational-dependent atelectasis is a common finding in the dependent portions of the lung using computed tomography (8,12,14,17,18) and has been investigated in animal studies and patients using a variety of other modalities including H 3 He MR (7)(8)(9)(10)(12)(13)(14)18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heart and abdomen also contribute to the greater compression of the posterior lung regions in the supine position (23). Gravitational-dependent atelectasis is a common finding in the dependent portions of the lung using computed tomography (8,12,14,17,18) and has been investigated in animal studies and patients using a variety of other modalities including H 3 He MR (7)(8)(9)(10)(12)(13)(14)18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is generally homogeneous distribution of the MR signal throughout the lung in healthy subjects following inhalation of the gas, small peripheral ventilation defects in the dependent areas of the lungs can been seen and are believed to be caused by collapse of small portions of the lung (3,5). The purpose of this study was to investigate the effect of patient positioning and time on the frequency, size and location of these defects, in order to better understand their impact and significance in the diagnosis of pulmonary disease when using H 3 He MR. Our findings were compared with earlier work done in posture-dependence of lung function, in animal studies and patients, using a variety of other modalities (7)(8)(9)(10)(12)(13)(14)18,19).…”
Section: Introductionmentioning
confidence: 88%
“…A major limitation in this area is the lack of a method to obtain quantitative, high-resolution maps of lung ventilation and perfusion with the subject in different orientations. Despite minimal orientation possible within the confines of a traditional human MRI scanner, some initial studies have shown that posture changes from supine (face up) to prone (face down) and to decubitus (sideways) affect the lung physiology in a way that can be clearly probed by 3 He MRI (18). Very-low-field 3 He MRI incorporating novel, open-access magnet designs can provide this area of pulmonary physiology with a powerful tool for studying orientational and posture-related effects.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the development for intensity inhomogeneity correction has been applied to MRI of neuroanatomy, where many techniques require a classification or segmentation step identifying the gray matter, white matter, and cerebrospinal fluid regions (16), a scenario that does not apply to helium-3 lung image data. With helium-3 image data, in addition to the amplitude of radiofrequency field, there are other potential contributions to intensity nonuniformity, such as the anatomic diffusion gradient (17) and posturerelated dependencies (18). In general, we tend to observe a low-frequency intensity variation toward the posterior of the lung and, although we do not know the relative contribution of these factors to the overall nonuniformity, we have found that application of our bias-correction algorithm improves image processing performance.…”
Section: Retrospective Bias Field Correctionmentioning
confidence: 99%